Jakość wód podziemnych zlewni bezpośredniej Jeziora Sławskiego = The quality of the underground water of the Lake Sławskie direct drainage basin - Małecki, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the years 1999-2003, researches of the level and quality of the under-ground water of the Lake Slawskie direct drainage basin were done. Trends concerning changes of the underground water quality, its level and level of the Lake Slawskie water, have been presented and analysed in charts.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); poziom wód gruntowych; jakość wód gruntowych; level of ground water; quality of ground water